Nutritional component of Barbonymus balleroides: A wild fresh water fish from Indonesia - SYAHFITRI ANITA; HARYONO HARYONO; GEMA WAHYUDEWANTORO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Anita S, Haryono, Wahyudewantoro G. 2019. Nutritional component of Barbonymus balleroides: A wild fresh water fish from Indonesia. Biodiversitas 20: 581-588. Barbonymus balleroides is a native species of fish from Indonesia that threatens by overfishing activity and habitat damage whereas little is known about its nutritional information. This study aimed to evaluate the nutritional content of wild barb fish that was collected from two different sites in Indonesia. Fishes were collected from Serayu and Cipunagara River. The body part of fishes was grouped and weighted to identify the ratio. Proximate composition was determined for flesh and byproduct parts. Flesh parts of fish were then examined for mineral content, fatty acid, and amino acid profile. Barb fish samples mainly form Cipunagara River contain high protein compare to several Indonesian freshwater fishes that commonly consumed. Flesh samples from both fish group were the heaviest part followed by its edible byproduct that often wasted. The amount of moisture and protein were higher in the flesh parts while byproduct showed higher content of fat and ash. Both samples contained a dominant amount of macro elements K and P. Fatty acid profile of flesh samples showed essential fatty acid that is good for human health. Amino acid profile showed the most dominant amino acid found in both samples was glutamic acid.